A Novel CRLH-CP Antenna with the Capability to be Integrated Inside RF Components for RF Electronic Devices and Embedded Systems - Alibakhshi-Kenari, Mohammad; Naser-Moghaddasi, Mohammad (Applied Computational Electromagnetics Society Journal (ACES), 2021)
In this paper, design and manufacturing of a composite right/left-handed carved planar (CRLH-CP) antenna with ? ? constitutive parameters is introduced. The composite right/left-handed transmission line (CRLH-TL) is introduced as a general TL possessing both left-handed (LH) and righthanded (RH) natures. The proposed antenna is constructed of four CRLH unit cells, each of which occupies space of 0.004?0×0.01?0×0.001?0, where ?0 is free space wavelength at 0.5 GHz. The antenna practical bandwidth is 120%, so that the proposed antenna can be used for frequency band from 0.5 GHz to 2 GHz in measurement. Also, the antenna gains and radiation efficiencies at the operational frequencies f=0.7, 1.5 and 2 GHz are 3.8 dBi and 53%, 4.85 dBi and 68.5%, and 4.3 dBi and 60.2%, respectively. According to the results, the proposed minimized ultra wideband (UWB) antenna is a good candidate to use in the RF electronic devices and embedded systems.